Cytotoxic Effects of Pistacia Atlantica (Baneh) Fruit Extract on Human KB Cancer Cell Line - Jaafari-Ashkvandi, Zohreh; Shirazi, Saeed Yousefi; Rezaeifard, Somayeh; Hamedi, Azadeh; Erfani, Nasrollah (Acta medica (Hradec Kralove), 2019)
Plants with anticancer properties are considered as cancer preventive and treatment sources, due to their some biological effects. Apoptosis induction and anti-proliferative effects of Baneh extract on various cancer cell lines have been reported. Hence, this study was designed to evaluate the cytotoxic effects of this fruit on KB and human gingival fibroblast cell lines (HGF). KB and HGF cells were treated with various concentrations of ethanolic Baneh extract and cisplatin as positive control. Cytotoxic activity and apoptosis induction were investigated using WST-1 and Annexin V assays. Data were analyzed using ANOVA and student's t-tests. IC50 after 24 and 48 hours treatment were respectively 2.6 and 1 mg/mL for KB cell line, and 1.5 and 1.6 mg/mL for HGF cell. During 48 hours Baneh extract induced apoptosis without significant necrosis, in a time- and dose-dependent manner. The induction of apoptosis in KB cells was significantly higher than HGF. It seems that ethanolic extract of Baneh contains compounds that can suppress KB cell growth through the induction of apoptosis. Within 48 hours, less cytotoxic effects were observed on normal fibroblast cells; therefore, it might be a potential anticancer agent.
Keywords: regulace genové exprese u nádorů; pistacia; Carcinoma, Squamous Cell; proliferace buněk; apoptóza; Female; squamous cell carcinoma; cytotoxicity; apoptosis; Gingiva; Apoptosis; ženské pohlaví; rostlinné extrakty; Gene Expression Regulation, Neoplastic; fytogenní protinádorové látky; gingiva; lidé; nádory děložního čípku; Antineoplastic Agents, Phytogenic; spinocelulární karcinom; fibroblast; Cell Proliferation; Plant Extracts; Uterine Cervical Neoplasms; KB buňky; cell line; Pistacia; KB Cells; Humans